CYSTOSTOMY DIVERSION REDUCED COMPLICATIONS FOLLOWING HYPOSPADIAS REPAIR: A SYSTEMATIC REVIEW AND META-ANALYSIS - Wahyudi, Irfan; Raharja, Putu Angga Risky; Situmorang, Gerhard Reinaldi; Rodjani, Arry (Indonesian Urological Association, 2024)
Objective: This study aims to investigate the associations between the use of cystostomy diversion and the incidence of complications following hypospadias repair. Material & Methods: An extensive search of PubMed, ScienceDirect, Embase, and the Cochrane Library, was performed to identify studies that assessed the impact of cystostomy diversion on complication rates after hypospadias repair. To evaluate potential biases, the RoB 2 tool was applied for randomized controlled trials (RCTs), while the ROBINS-I tool was used for observational studies. Data analysis was conducted using Review Manager 5.4. Results: This review included ten studies involving 1.120 patients who underwent hypospadias repair. The overall complication was 16.9%. The meta-analysis revealed that opting against cystostomy diversion after hypospadias repair led to a notably increased risk of complications, as evidenced by a pooled odds ratio (OR) of 1.48 (95% confidence interval (CI) 1.07–2.03). The significant negative effect of not performing cystostomy on the risk of complications was consistent in sub-analysis of distal hypospadias (OR 1.97; 95% CI 1.11–3.51) and primary hypospadias repair (OR 1.80; 95% CI 1.19–2.73). In the funnel plot, there was no significant publication bias identified. Conclusion: Our meta-analysis demonstrated that cystostomy diversion reduces the incidence of complications following hypospadias repair. The positive effects were consistent in both distal hypospadias and primary hypospadias repair. Keywords: Complications, cystostomy, hypospadias.